2022
DOI: 10.3389/fimmu.2022.908749
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Adipose Tissue Macrophages in Human Disease

Abstract: Macrophages are a population of immune cells functioning in antigen presentation and inflammatory response. Research has demonstrated that macrophages belong to a cell lineage with strong plasticity and heterogeneity and can be polarized into different phenotypes under different microenvironments or stimuli. Many macrophages can be recruited by various cytokines secreted by adipose tissue. The recruited macrophages further secrete various inflammatory factors to act on adipocytes, and the interaction between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 108 publications
2
17
0
Order By: Relevance
“…ATMs exhibit chronic metabolic dysfunction, procoagulant activity and anti-fibrinolytic properties [51,52], but their ability to regulate anticoagulant pathways remains unknown. Using an existing transcriptomic dataset [53] of ATMs isolated from CD and HFD-fed mice, we found that ATMs from HFD-fed mice exhibit an “M1-like” phenotype, with several established canonical M1 genetic markers ( tnf , Il1b , Nos2 , CD80 ) significantly upregulated compared to mice fed a normal diet (Figure 5b and Supplementary Table 2) , which is in keeping with previous literature [51,53,54]. Additionally, both F10 and SERPINE1 expression was significantly increased in ATMs from HFD-fed mice (Figure 5b and Supplementary Table 2) .…”
Section: Resultssupporting
confidence: 89%
“…ATMs exhibit chronic metabolic dysfunction, procoagulant activity and anti-fibrinolytic properties [51,52], but their ability to regulate anticoagulant pathways remains unknown. Using an existing transcriptomic dataset [53] of ATMs isolated from CD and HFD-fed mice, we found that ATMs from HFD-fed mice exhibit an “M1-like” phenotype, with several established canonical M1 genetic markers ( tnf , Il1b , Nos2 , CD80 ) significantly upregulated compared to mice fed a normal diet (Figure 5b and Supplementary Table 2) , which is in keeping with previous literature [51,53,54]. Additionally, both F10 and SERPINE1 expression was significantly increased in ATMs from HFD-fed mice (Figure 5b and Supplementary Table 2) .…”
Section: Resultssupporting
confidence: 89%
“…Preventing the ability of macrophages from transitioning to the M2 state leads to accelerated weight gain and glucose intolerance in mice [76,77]. M2 macrophages can maintain insulin sensitivity and glucose homeostasis by secreting factors such as IL-10, IL-1, and catecholamines to regulate lipid metabolism, block inflammation response, and increase insulin sensitivity [78][79][80]. Although conflicting evidence suggests that M2 macrophages do not contribute to adipocyte metabolism or adaptive thermogenesis via the production of catecholamines [81], evidence also shows that macrophages in adipose tissue are capable of taking up and degrading catecholamines released by neurons and that this system could be improved by obesity and aging, resulting in a decreased response to cold stress and starvation [82,83].…”
Section: Adipose Tissue and Atmsmentioning
confidence: 99%
“…In human obese AT, pro-inflammatory macrophages have been described as CD14 + CD16 + cells with high levels of M1 markers ( 91 ). Polarization of inflammatory monocytes has been implicated in the pathogenesis of obesity-related diseases including T2DM and atherosclerosis ( 92 , 93 ), thus underlying mechanisms and approaches for resolving monocyte polarization conducive to disease regression need to be established.…”
Section: Discussionmentioning
confidence: 99%